2004
DOI: 10.1590/s0103-84782004000300015
|View full text |Cite
|
Sign up to set email alerts
|

Atividade polifenoloxidase e compostos fenólicos em pós-colheita de pêssegos cultivado em pomar com cobertura vegetal e cultivo tradicional

Abstract: RESUMO Estudou-se o efeito do manejo do solo, com e sem cobertura vegetal, na atividade da polifenolaxidase e compostos fenólico em pêssegos cvs. Chimarrita e Cerrito, durante o armazenamento refrigerado. As frutas foram colhidas em três INTRODUÇÃOAs principais causas de perdas após a colheita de pêssegos são a ocorrência de podridões e de distúrbios fisiológicos. Estes últimos manifestam em maior intensidade durante o armazenamento refrigerado. Os distúrbios fisiológicos mais comuns são a lanosidade e o escur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
3
Order By: Relevance
“…Variações nos fenóis totais foram verifi cados em porta-enxertos de pessegueiro também por Giorgi et al (2005) e Remorini et al (2008. Combinações de fenóis tendem a se acumular no tecido epidérmico de plantas como forma de proteção contra a radiação (Dixon & Paiva, 1995), o que pode causar distúrbios fi siológicos no armazenamento, como, por exemplo, o escurecimento interno (Martins et al, 2004). A época de maturação foi semelhante entre os porta-enxertos.…”
Section: Resultsunclassified
“…Variações nos fenóis totais foram verifi cados em porta-enxertos de pessegueiro também por Giorgi et al (2005) e Remorini et al (2008. Combinações de fenóis tendem a se acumular no tecido epidérmico de plantas como forma de proteção contra a radiação (Dixon & Paiva, 1995), o que pode causar distúrbios fi siológicos no armazenamento, como, por exemplo, o escurecimento interno (Martins et al, 2004). A época de maturação foi semelhante entre os porta-enxertos.…”
Section: Resultsunclassified
“…The total peach phenols were 253.4±0.05 mgGAE.100g Martins et al (2004) observed differences in the total phenol content of peaches during ripening, noting that there was an increase in the content of these compounds according to the degree of ripening, as peaches in the semi-ripe and ripe stage presented higher phenol content than the fruits harvested in the green stage. Therefore, the content of phenolic compounds found in the peach in the present study may be related to the degree of fruit ripeness and, consequently, with soluble solid content and acidity (Table 1).…”
Section: Resultsmentioning
confidence: 79%
“…Segantini et al (2012) found levels of polyphenols ranging from 53.38 to 141.77 mg GAE.100g -1 of pulp when analyzing yellow peaches, and 'Douradão' presented the lowest content, while 'Big-Aurora' showed the highest content of polyphenols. Martins et al (2004) observed differences in the total phenol content of peaches during ripening, noting that there was an increase in the content of these compounds according to the degree of ripening, as peaches in the semi-ripe and ripe stage presented higher phenol content than the fruits harvested in the green stage. Therefore, the content of phenolic compounds found in the peach in the present study may be related to the degree of fruit ripeness and, consequently, with soluble solid content and acidity (Table 1).…”
Section: Physical-chemical Analyses Antioxidant Activity Phenols Amentioning
confidence: 83%